CONFORMATIONAL ANALYSIS AND STEREOCHEMICAL CONTROL IN MACROLIDES BY MOLECULAR MECHANICS AND BOLTZMANN DISTRIBUTION - Fatima, Daissa, Belaidi Salah; Touhami, Lanez (university of eloued جامعة الوادي, 2023)
The Conformational analysis and stereochemical control of 20 Membered Macrolides were investigated using molecular mechanics calculations, PM3 semi empirical method, and Boltzmann distribution. The results indicate that these macrocycles have a high degree of conformational flexibility. However, in the presence of tricarbonyliron, the number of favorable conformations was reduced to only four. The study also revealed significant diastereoselectivity (73:27) in B type complexed macrolides. Furthermore, it wa s observed that the methyl group in position α 2 had a local conformational effect that increased the diastereoselectivity of alkylation reactions. The high diastereoselectivity observed was attributed to the combination of stereochemical remote control wit h Fe(CO) 3 and local control by the methyl group
artecal
Keywords: Macrolide, Molecular me chanics, PM 3 , Boltzmann distribution, Stereoselectivity